2018
DOI: 10.1007/s12026-018-9062-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel third-generation TSH receptor antibody (TRAb) enzyme-linked immunosorbent assay based on a murine monoclonal TSH receptor-binding antibody

Abstract: TSH receptor (TSHR) autoantibody (TRAb) is the serological hallmark of Graves' disease (GD). Third-generation enzyme-linked immunosorbent assays (ELISAs) using monoclonal TRAbs instead of TSH have been found useful for TRAb analysis recently. For the first time, a mouse monoclonal antibody (mAb) against TSHR was analyzed for TRAb detection and compared with human mAb M22 and TSH by the same competitive binding assay technique. A mouse monoclonal antibody (T7) binding to the TSH receptor and inhibiting TSH bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We included all the studies discussing the relationship between the night shift work and the thyroid disorders during the last ten years. Although the shift work is under investigation for many decades, we decided to restrict our analysis to a short timeframe since the 3rd generation assay, which has spread worldwide in the last 10 years, now ensures an excellent analytical sensitivity, able to determine very low TSH concentrations (Roggenbuck et al 2018). No restrictions were considered regarding age, sex, language, and ethnicity of the population.…”
Section: Methodsmentioning
confidence: 99%
“…We included all the studies discussing the relationship between the night shift work and the thyroid disorders during the last ten years. Although the shift work is under investigation for many decades, we decided to restrict our analysis to a short timeframe since the 3rd generation assay, which has spread worldwide in the last 10 years, now ensures an excellent analytical sensitivity, able to determine very low TSH concentrations (Roggenbuck et al 2018). No restrictions were considered regarding age, sex, language, and ethnicity of the population.…”
Section: Methodsmentioning
confidence: 99%
“…Although a positive TRAb test result suggests the presence of TSAb or TBAb, it is reasonable to presume that a positive result in a patient with hyperthyroidism is due to TSAb. TSAb behaves like TSH and stimulates the synthesis of thyroid hormone by binding to TSHR, which leads to hyperthyroidism [ 8 ]. TSAb also causes diffuse, hypervascular goiter in many GD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse monoclonal TRAb T7 recognizing the TSH binding site of the TSHR was employed for the detection of TRAb in human sera by a novel 3 rd -generation RIA technique. Human TSHR was immobilized to polystyrene tubes by a mouse monoclonal TRAb not interfering with the TSH-binding site as reported elsewhere [20]. In contrast to the current two-step TRAb RIA procedure, 100 µL of neat patient serum or calibrators were simultaneously incubated with 50 µL of start buffer and 100 µL of 125 I-labelled T7 in the TSHR coated tubes at RT for 2 hours while shaking.…”
Section: Third Generation One-step Trab Riamentioning
confidence: 99%
“…The human stimulating monoclonal TRAb M22 was the first to be used in an ELISA to detect TRAb [25,33]. It was later shown that other monoclonal TRAb, such as the murine T7, were not inferior to the former in similar assay designs [20].…”
Section: Introductionmentioning
confidence: 99%